Desarrollo de un plan de infraestructura tecnológica para el departamento de TIC de la UTMACH - Vega Delgado, Gabriel Jesús; Ambrosi Castro, Acxel Andrés (Machala; Universidad Técnica de Machala, 2024)
The management and maintenance plan for the technological infrastructure of the ICT department at UTMACH had as its main objective to address the administration and allocation of IT assets in areas such as applications, software, hardware, networks, and servers. Additionally, the plan aimed to improve processes and establish policies to ensure compliance with operational and strategic activities aligned with internal organization regulations. Given all the aforementioned aspects, this graduation thesis focused on proposing policies and standardizing procedures, guided by national and international IT industry standards, norms, and best practices. To execute the prototype, a series of steps were implemented in collaboration with the ICT department. These steps included information gathering, establishment of standards for IT asset inventories, documentation of inventories, analysis of the current infrastructure situation, establishment of standards for plan resources, development of resources, establishment of standards for the technological infrastructure plan, and finally, the development of the plan itself. The plan development phase involved creating various resources or documents supporting the main plan. Once these backup documents were developed and approved, they were utilized to formulate the policies and structure of the technological infrastructure plan. For the prototype evaluation, the expert evaluation technique was employed. Eight engineers with experience in IT management and governance were selected for this purpose, and they assessed the proposed procedures and policies. Ultimately, it was confirmed that the technological infrastructure plan met the objective of proposing policies and procedures aligned with industry norms, standards, and best practices for the management and maintenance of IT assets
El plan de gestión y mantenimiento de la infraestructura tecnológica para el departamento de TIC de la UTMACH, tenía como principal objetivo solucionar la administración y asignación de activos de TI de ámbitos como aplicaciones, software, hardware, redes y servidores. Además, con el plan se buscaba mejorar procesos y establecer políticas para garantizar el cumplimiento de actividades operativas y estratégicas alineadas a regulaciones internas de la organización. Por todo lo planteado, el presente trabajo de titulación se enfocó en la proposición de políticas y estandarización de procedimientos; regidos por estándares, normas y buenas prácticas de la industria de TI nacionales e internacionales. Para la realización del prototipo se implementó una serie de pasos definidos en conjunto con el departamento de TIC, dichos pasos son: recopilación de información, establecimiento de normas para los inventarios de activos de TI, documentación de inventarios, análisis de la situación actual de la infraestructura, establecimiento de normas para los recursos del plan, desarrollo de los recursos, establecimiento de normas para el plan de infraestructura tecnológica y finalmente el desarrollo de este. La etapa de desarrollo del plan se caracterizó por el desarrollo de varios recursos o documentos que sustenten el plan principal, una vez desarrollados y aprobados los documentos de respaldos fueron utilizados para realizar las políticas y la estructura del plan de infraestructura tecnológica. Para la evaluación del prototipo se utilizó la técnica de evaluación de expertos, para esto se seleccionó 8 ingenieros con experiencia en gestión y gobernanza de TI y se evaluaron los procedimientos y políticas propuestos. Finalmente se comprobó que el plan de infraestructura tecnológica cumplía el objetivo de proponer políticas y procedimientos, alineados a normas, estándares y buenas prácticas de la industria, para la gestión y mantenimiento de activos de TI
Keywords: GESTION INFORMATICA; INFRAESTRUCTURA TECNOLOGICA; SEGURIDAD INFORMATICA; POLITICA DE TIC